The Post-Chevron Law of Deference for Investor-State Arbitration - Won L. Kidane (Washington University Global Studies Law Review, 2025)
In Loper Bright Enterprises v. Raimondo, the United States Supreme Court clarified the “law of deference” built “on the foundation laid in Chevron.” The American conception of the law of deference, long solidified as the Chevron doctrine, has had extraordinary resonance, having been cited in at least 18,000 cases and 22,000 publications over a period of forty years. The Court’s overruling of the two-step Chevron analysis for the resolution of statutory ambiguity is the most obvious outcome and is likely to attract the most attention. There is, however, an obscure aspect of the Court’s overruling of Chevron: the clarification of the concept of deference as a rule of decision, a legal imperative, rather than as a mere standard of review.
Keywords: Chevron doctrine; Chevron; Loper Bright Enterprises v. Raimondo; law of deference; Chevron analysis; Investor-State Arbitration